2021
DOI: 10.1111/imm.13433
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood‐based measurement of SARS‐CoV‐2‐specific T cells reveals asymptomatic infection and vaccine immunogenicity in healthy subjects and patients with solid‐organ cancers

Abstract: Accurate assessment of SARS‐CoV‐2 immunity is critical in evaluating vaccine efficacy and devising public health policies. Whilst the exact nature of effective immunity remains incompletely defined, SARS‐CoV‐2‐specific T‐cell responses are a critical feature that will likely form a key correlate of protection against COVID‐19. Here, we developed and optimized a high‐throughput whole blood‐based assay to determine the T‐cell response associated with prior SARS‐CoV‐2 infection and/or vaccination amongst 231 heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Higher incidence and/or worse outcomes in the context of in vivo COVID-19 infection in people receiving anti-CD20, [5,6] and fingolimod,[7] have been observed in some large population-based studies performed prior to the widespread availability of booster vaccines. These observations require further study to fully understand the clinical implications of booster vaccination and their underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Higher incidence and/or worse outcomes in the context of in vivo COVID-19 infection in people receiving anti-CD20, [5,6] and fingolimod,[7] have been observed in some large population-based studies performed prior to the widespread availability of booster vaccines. These observations require further study to fully understand the clinical implications of booster vaccination and their underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood samples were incubated at 37°C for 20-24 hours before harvesting plasma from each sample to quantify IFN-g by ELISA (BioLegend). SARS-CoV-2-specific T-cell responses were identified as positive using previously defined criteria for differentiating naïve controls from prior COVID-19 vaccinated and/or infected individuals (sensitivity 96.0% and specificity 84.4%) [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of viral infections such as influenza have reported that physical distancing is effective at limiting disease spread, a scenario certainly influential for the protection of COVID-19 infections. The most effective preventive measure for deadly contagious diseases, including COVID-19, is vaccination, which fundamentally boosts the immune system, especially in susceptible populations [ 145 , 146 ]. Vaccines allow for preemptive development of memory B- and T-cells to neutralize pathogens; however, the efficacy of vaccines depends on age, existing immunity, underlying medical conditions, and/or and immunological disorders.…”
Section: Therapeutic Approaches For the Prevention And Treatment Of C...mentioning
confidence: 99%